A Rare and Lethal Ostial Left Main Trunk Lesion: A Case Report. Issue 1 (15th March 2022) - Huang, Baotao; Zhang, Ran; Li, Chen
Abstract : Abstract: Coronary artery involvement in cardiovascular syphilis is infrequent and often overlooked, especially in patients with latent syphilis. Herein, we present the case of myocardial infarction largely related to cardiovascular syphilis in a 63-year-old man. Invasive coronary angiography and contrast-enhanced computed tomography scan revealed a critical ostial narrowing of the left main trunk, an occlusive right coronary artery, and moderate-to-severe ostial stenosis of multiple major branches of the abdominal aorta. Syphilis screening and confirmatory tests were positive. Cardiovascular syphilis was considered. Percutaneous coronary intervention (PCI) was performed uneventfully, and a coronary stent was implanted in the ostium of the left main coronary artery. However, on day 3 after PCI, the patient died suddenly, likely because of stent thrombosis. In conclusion, severe coronary lesions confined to the ostia suggest rheumatologic large-vessel vasculitis or infectious aortitis.